If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 = 2v + -3v Combine like terms: 2v + -3v = -1v 4 = -1v Solving 4 = -1v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add 'v' to each side of the equation. 4 + v = -1v + v Combine like terms: -1v + v = 0 4 + v = 0 Add '-4' to each side of the equation. 4 + -4 + v = 0 + -4 Combine like terms: 4 + -4 = 0 0 + v = 0 + -4 v = 0 + -4 Combine like terms: 0 + -4 = -4 v = -4 Simplifying v = -4
| -113=6(2r-5)+1 | | 5+5y+7= | | 3p-2=31 | | -8c+6=1 | | 6X+8+3X-2=-132 | | v+9*3=8 | | -156=-6-5(6+6n) | | -210-5x=-0 | | -5x-6=-2 | | 49s^2=64 | | -8(8-x)=4/5(x-10) | | -1=5+x*6 | | 784=-4x^2+800 | | 800-300= | | P=-30t^2+450t-790 | | -4=r*20-5 | | x^2y^2-x^2= | | 8x+1=4x+3 | | -6(8x+3)-6x=90 | | 0=4+n*5 | | 4b+7= | | 2x+4x+3x+3x=360 | | 5+3n+7=3 | | 4(x-3)=6x+5-3x | | 6(J+3)=102 | | -6m-5(1+3m)=163 | | x+120=24-5x | | 2b+3c=57 | | 15=-4v-v | | -(3n-8)+2=-5(n-3)-(5-4n) | | (6-5)-(2*3-9)+2= | | -31+x=38+4x |